KPK Corner as Library Service in Supporting Anti-Corruption Education in Telkom University Open Library - Neneng Komariah; Encang Saepudin; Rizki Nurislaminingsih (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
Anti-corruption education is an attempt to prevent corruption. One of the targets of anti-corruption education is students. The university library can contribute to supporting anti-corruption education through the provision of relevant information sources. For this requirement, KPK as an institution responsible for combating corruption gives the KPK Corner as a grant to the selected university library. This study aims to determine the process of obtaining KPK Corner grants, and the development of KPK Corner in Open Library Telkom University. The research method used is qualitative methods with descriptive analysis. Data collection techniques using interviews, observations, and library studies. The results showed that the process of obtaining KPK Corner grants was conducted by submitting proposals as an initiative of the Open Library. Furthermore, approaches to the associated KPK staff. After almost two years of waiting, finally Open Library get KPK Corner. The KPK Corner grants are also an award for Telkom University who cares deeply about anti-corruption education and conducting various anti-corruption campaigns. Furthermore, for the management, services and promotions of KPK Corner are the responsibility of the Open Library. The presence of KPK Corner is proof of the spirit of Open Library staff to conduct library development through cooperation. It is an aspect assessed in the library accreditation process. Therefore, the Open Library can inspire other libraries.